2016
DOI: 10.1038/srep28584
|View full text |Cite
|
Sign up to set email alerts
|

Firing frequency and entrainment maintained in primary auditory neurons in the presence of combined BDNF and NT3

Abstract: Primary auditory neurons rely on neurotrophic factors for development and survival. We previously determined that exposure to brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT3) alters the activity of hyperpolarization-activated currents (Ih) in this neuronal population. Since potassium channels are sensitive to neurotrophins, and changes in Ih are often accompanied by a shift in voltage-gated potassium currents (IK), this study examined IK with exposure to both BDNF and NT3 and the impact on fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Poststimulus facilitation in single auditory neurons extended to delays of 9-13 ms between the optical and electrical stimuli in vitro, which is greater than the facilitation observed in vivo. Dynamics and firing rates are generally slower in vitro, as found previously for electrical stimulation (Wright et al, 2016). Despite these differences, the observed facilitation both in vitro and in vivo suggests that cultured SGNs are a good in vitro model for hybrid optical stimulation.…”
Section: Hybrid Stimulationsupporting
confidence: 76%
“…Poststimulus facilitation in single auditory neurons extended to delays of 9-13 ms between the optical and electrical stimuli in vitro, which is greater than the facilitation observed in vivo. Dynamics and firing rates are generally slower in vitro, as found previously for electrical stimulation (Wright et al, 2016). Despite these differences, the observed facilitation both in vitro and in vivo suggests that cultured SGNs are a good in vitro model for hybrid optical stimulation.…”
Section: Hybrid Stimulationsupporting
confidence: 76%
“…Recordings from individual SGNs in mice have demonstrated peak discharge rates >1 kHz ( Taberner and Liberman, 2005 ), which then adapt to steady state levels >200 Hz, suggesting these neurons employ specialized mechanisms that support repetitive rapid spiking and ensure extremely short refractory periods. Patch clamp recordings and immuno-labeling experiments have suggested that the expression of numerous ion channel subtypes contributes to shaping the firing properties of SGNs, in mice and rats ( Jagger and Housley, 2002, 2003 ; Hossain et al, 2005 ; Wang et al, 2013 ; Crozier and Davis, 2014 ; Smith et al, 2015 ; Kim and Rutherford, 2016 ; Wright et al, 2016 ), and in guinea pigs ( Santos-Sacchi, 1993 ; Szabó et al, 2002 ). Following hearing onset, increases in firing rates and shortening of the refractory period are observed ( Wu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of growth factors in the inner ear can potentially improve the performance of cochlear implants based on animal models of cochlear implantation. The effect of growth factor infusion into the deaf inner ear can include enhancing the survival of neurons as well as all enhancing and altering the capacity for depolarization of the neurons (Wright et al, 2016). Translation of these observations into successful human studies will require understanding the pathophysiology of neuronal degeneration in human spiral ganglion cells as well as developing systems that restore physiologically relevant levels of growth factors to the inner ear.…”
Section: Discussionmentioning
confidence: 99%